Oral Health of Rural Cameroonian Children: A Pilot Study in Bamendou - Guillaume Aimond; Béatrice Thivichon-Prince; Célia Bernard-Granger; Coline Gisle; Tatiana Caron; Andre Valdese Jiokeng; Stefano Majoli; Jean-Christophe Maurin; Maxime Ducret; Laurent Laforest (MDPI AG, 2023)
Access to dental care in Cameroon is a public health issue, particularly for children living in rural areas. Given the lack of recent data, the investigation of children's oral health along with their oral hygiene behavior, needs in terms of care, and access to oral hygiene materials were investigated. This cross-sectional pilot study was conducted in Bamendou, Western Region of Cameroon. The study population included 265 children aged 3-18 years who completed a questionnaire about their oral hygiene practices. A clinical examination assessed dental caries, calculus, gingivitis, and oral hygiene. The Chi-squared test was used to identify potential factors influencing caries prevalence rates (significance threshold: p < 0.05). Among the 265 children (females: 41.5%, mean age 9.3 years), caries prevalence (ICDAS ≥ 2) was 78.5% and significantly increased with age: 62.2% (3-6 years), 80.9% (7-11 years) and 84.1% (12-18 years, p = 0.01). Virtually no children (95.1%) had ever visited a dentist. While only 23.4% of children brushed their teeth at least twice a day, 14% worryingly reported the use of products other than toothpaste (ash, soap, salt, or bicarbonate) and 13.6% no brushing product. The present study revealed a high prevalence of dental caries in this population and inadequate toothbrushing habits, which highlights the need for preventive oral health education and intervention to address these issues.